Prophylactic endoluminal vacuum-assisted therapy in high-risk ultra-low rectal anastomoses: a retrospective comparative study of feasibility and clinical outcomes - Nour Alkhanji; Eslam Elmaghraby; Saleh Lahes; Mohammed Abdulla; Wolfram Trudo Kneofel; Nadja C Lehwald-Tywuschik (BMC Surgery, 2026)
Abstract Background Anastomotic leakage (AL) remains a major cause of morbidity and mortality after ultra-low anterior resection (uLAR) for rectal cancer, when the anastomosis is located ≤ 5 cm from the anal verge, in patients with additionally risk factors. This study proposes the prophylactic endoluminal vacuum-assisted therapy (pEVAT) as a feasible strategy that may reduce AL incidence and promote healing in this subgroup of patients. Methods Thirty-three patients multiple established risk factors for AL who underwent uLAR with a diverting stoma were retrospectively analyzed. Thirteen patients received pEVAT intraoperatively using a polyurethane sponge, while twenty patients served as the control group. The main outcomes included AL rate, secondary outcomes were anastomotic stenosis, other postoperative complications, length of hospital stay as well as stoma reversal. Results Anastomotic leakage occurred in 7.7% of patients receiving pEVAT versus 30% in the control group. Unadjusted risk estimation demonstrated lower odds of leakage in the pEVAT group, but the difference was not statistically significant. Anastomotic stenosis was also observed in 7.7% of the pEVAT group compared to 35% of controls. The stoma reversal rate was higher in the pEVAT group (76.9% vs. 55%). Mean hospital stay was shorter (26 vs. 36 days). No mortality occurred in the pEVAT group, and complications were limited. Conclusion Prophylactic EVAT is a feasible and safe approach that may have a protective role against anastomotic complications in selected high-risk patients undergoing uLAR. Larger, prospective, and ideally randomized studies are required to clarify its clinical effect in this subgroup.